2012
DOI: 10.1038/ajg.2011.483
|View full text |Cite
|
Sign up to set email alerts
|

Use of Antidiabetic Agents and the Risk of Pancreatic Cancer: A Case–Control Analysis

Abstract: Use of metformin was associated with a decreased risk of pancreatic cancer in women only, whereas use of sulfonylureas and of insulin was associated with an increased risk of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 29 publications
2
91
2
3
Order By: Relevance
“…In the latter study, there were interactions between metformin and glibenclamide use towards lower cancer risk; after adjusting for the interaction terms, the use of glibenclamide provided no protective effect (HRZ1.27; 95% CI 0.76-2.11) (24). Some studies have not found an imbalance in cancer types among glibenclamide users (40), but others have found increased risks of pancreatic or hepatocellular carcinoma among sulphonylurea users (22,41,42). A recent meta-analysis, however, found no evidence that sulphonylureas affected the risk of cancer at any site (43).…”
Section: Glibenclamidementioning
confidence: 99%
“…In the latter study, there were interactions between metformin and glibenclamide use towards lower cancer risk; after adjusting for the interaction terms, the use of glibenclamide provided no protective effect (HRZ1.27; 95% CI 0.76-2.11) (24). Some studies have not found an imbalance in cancer types among glibenclamide users (40), but others have found increased risks of pancreatic or hepatocellular carcinoma among sulphonylurea users (22,41,42). A recent meta-analysis, however, found no evidence that sulphonylureas affected the risk of cancer at any site (43).…”
Section: Glibenclamidementioning
confidence: 99%
“…Table 1A summarizes epidemiological studies that show pancreatic cancer risk and cancer mortality associated with metformin use while Table 1B presents observational studies and clinical trials on overall cancer risk and mortality in relation to metformin use. While some studies show a reduction in pancreatic cancer [35][36][37][38][39] and overall cancer risk [37,[39][40][41][42][43][44][45] among diabetic metformin users, there are also studies that report no significant difference in cancer risk among diabetics who take metformin compared to patients who take other anti-diabetic treatments [36,[46][47][48][49][50][51]. These conflicting results may be explained by differences in the study population, the confounding factors accounted for during statistical analysis and the selected study design (e.g., cohort versus case-control).…”
Section: Chemopreventive Properties Of Metforminmentioning
confidence: 61%
“…Many studies support the notion that the use of metformin results in lower incidence of cancer [71][72][73][74][75]. Lung, pancreatic, prostate, breast, ovarian, and hepatocellular cancer incidence has been found to be lower among patients receiving metformin [76][77][78][79][80][81][82]. Moreover, the mortality from cancer was lower in diabetes patients taking metformin as part of their anti-diabetic medication compared with those not taking metformin [83][84][85][86].…”
Section: Metformin Cancer Prevention and Mortalitymentioning
confidence: 77%